Not Only by Accident. Arthur Koestler’s Reception in Post-war Hungary, 1945–1948 - Zénó Vernyik (Acta Universitatis Sapientiae: Philologica)
This article is the first part of a series of publications on Arthur Koestler’s reception in Hungary during its transition to Communism. Given the author’s iconic status as an anti-Communist writer, it is reasonable to suppose that his texts would have been banned and his name rarely uttered, much less printed, in Hungary before the 1989 regime change. It is thus not surprising that this view is virtually uncontested by scholars both in Hungary and beyond. Yet, as shown here on the basis of thirtyone articles published between April 1945 and June 1948 in Hungarian dailies, journals, and magazines, at least in this early and transitional period, Koestler’s writing is not only frequently mentioned but actively discussed. Furthermore, through a closer analysis of the contents of these texts, five specific categories of mentions are identified: (1) Koestler cited as a journalist reporting on contemporary events; (2) his opinion quoted as that of an authority figure; (3) polemics towards Koestler’s views; (4) reports on the foreign reception of Hungarian literature, including Koestler; and (5) Koestler used as a public scapegoat.